Hydrocarbon exploration in the case of the Malvinas Island from 1995 to 2022 - Berardi, Lilián (2024)
This paper aims to analyze the hydrocarbon exploration process in the Malvinas Islands carried out by the United Kingdom from 1995 to 2022. In relation to this, the question of the Malvinas Islands refers to a dispute between the Argentine and British governments over sovereignty over the Malvinas Islands and islands of the South Atlantic, the surrounding marine spaces, which also includes oil and gas. In this sense, these resources hosted on the islands’ submarine shelf were a long-standing focus of interest. In the 1990s, the British government authorized the arrival of transnational companies to carry out exploration activities and possible exploitation in an area that is still under international dispute. In this context, the Argentine State recognized these insular and maritime areas as an integral part of its national territory and, consequently, rejected the presence of these companies and declared their activities illegal.